Effects of Prostacyclin and of the Stable Prostacyclin Analogue ZK 36374 on Forearm Blood Flow and Blood Platelet Behaviour in Man - Cowley, A J; Heptinstall, S; Hampton, J R (Thrombosis and Haemostasis, 1985)
PGI2 and ZK 36374 were each infused into volunteers and the effects on forearm blood flow and on platelet behaviour were determined. Infusions of PGI2 or ZK 36374 did not alter resting forearm blood flow but both agents reduced the extent of the vasoconstriction that occurred in response to cold. ZK 36374 appeared to be a much more potent inhibitor of platelet behaviour than PGI2 when blood was taken while the infusions were in progress, but the effects of both agents were no longer evident one hour after the infusions were terminated. There was an inverse relationship between the extent of cold-induced vasoconstriction and the concentration of sodium arachidonate that was needed to induce platelet aggregation for different individuals. Infusions of PGI2 affected both parameters equally but ZK 36374 had a greater effect on platelet behaviour than on blood flow. It is possible that very low doses of ZK 36374 would result in inhibition of platelet behaviour without producing adverse haemodynamic effects.
Keywords: Prostacyclin; ZK 36374; Blood platelets; Blood vessels